Pengaruh Financing To Deposit Ratio Dan Dana Pihak Ketiga Terhadap Pembiayaan Musyarakah Pada Bank Umum Syariah Dengan Non Perfoming Financing Sebagai Variabel Moderasi - Devi Rahmawati; Titin Agustin Nengsih; Addiarahman Addiarahman; Novi Mubyarto (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This study aims to examine the effect of Financing to Deposit Ratio (FDR) and Third Party Funds (DPK) on Musyarakah Financing at Islamic Commercial Banks with Non-performing financing (NPF) as a moderating variable. A quantitative approach is used by utilizing documentary studies using secondary data from the annual financial statements of each Islamic Bank in Indonesia from 2018 to 2022. Sampling was done purposively by selecting 11 banks as samples. The data analysis method used is moderated regression analysis (MRA). The hypotheses in this study are: (1) FDR affects the distribution of Musyarakah financing in Islamic commercial banks, (2) DPK affects the distribution of Musyarakah financing in Islamic commercial banks, (3) NPF moderates the effect of FDR on the distribution of Musyarakah financing, and (4) NPF moderates DPK on the distribution of Musyarakah financing. The results showed that: (1) FDR has a negative and significant effect on Musyarakah Financing in Islamic commercial banks, (2) DPK has a positive and significant effect on profitability in Islamic commercial banks in Indonesia, (3) NPF does not moderate the effect of FDR on Musyarakah Financing, and (4) NPF moderates the effect of DPK on Musyarakah Financing in Islamic commercial banks in Indonesia.